Pengaruh Pembelajaran Berbasis Biomimicry Design Terhadap Kreativitas dan Innovative Thinking Skills Siswa SMK Dalam Merancang Mesin Berkelanjutan: The Impact of Biomimicry Design-Based Learning on Vocational Students’ Creativity and Innovation in Sustainable Machine Design - Islami Fatwa; Nurul Fadieny; Riza Andriani; Widya; Farhan; Taufik Baga Manihuruk (Jurnal Pendidikan Teknik Mesin Undiksha, 2026)
This study aims to examine the effect of biomimicry design-based learning on the creativity and innovative thinking skills of vocational high school students in designing sustainable machines. The research employed a quasi-experimental approach with a One-Group Pretest–Posttest design. The participants were eleventh-grade students from the mechanical engineering program at SMK Negeri 1 Muara Batu. Research instruments included a creativity test and an innovative thinking skills rubric, both validated by experts. Data were analyzed using Repeated Measures MANOVA to determine differences in students’ abilities before and after the implementation of the learning model. The results indicated a significant difference between the pretest and posttest scores (p < 0.001), with a partial eta squared value of 0.943, demonstrating a very strong effect. These findings suggest that biomimicry design-based learning effectively enhances students’ creativity and innovative thinking through exploration of natural principles, collaboration, and contextual problem solving. Overall, this learning approach is proven effective in developing higher-order thinking skills and has great potential to serve as a sustainable and industry-relevant model for vocational education in the future.